Pathogenesis of a Systemic Inflammatory Reaction: New Aspects - AA. Fursov; A.B. Salmina; A. G. Sokolovich; K. Yu. Belyaev; A. I., Inzhutova; NA. Malinovskaya; S.V. Shakhmayeva; S.V. Mikhutkina; A.V. Danilovich (Общая реаниматология, 2008)
The currently available data on the pathogenesis of a systemic inflammatory reaction (SIR) are reviewed in terms of dys-regulation of membrane-cytoskeletal interactions, cellular adhesion, membrane particle release, and development of endothelial dysfunction as a key factor in the genesis of SIR. Key words: systemic inflammatory reaction, membrane particles, blebbing, selectines, cytokines.